Enforcement of Islamic Criminal Law is a Concrete Solution to Eradicate Corruption - Salsabila, Adzanah Mariska Salsabila; Anggara, Zaky; Hasan, Firdaus (Institut Agama Islam Negeri Kendari, 2026)
The persistence of systemic corruption in Indonesia highlights the structural inadequacy of positive law in confronting extraordinary crime. Data from Indonesia Corruption Watch (ICW) show that in 2023 there were 791 corruption cases involving 1,695 suspects, causing potential state losses of Rp56 trillion, which escalated dramatically in 2024 to Rp279.9 trillion. This escalation reflects not merely weak law enforcement, but a deeper normative failure in the construction and orientation of positive criminal law, which remains predominantly formalistic and punitive without effectively addressing the social harm and breach of public trust inherent in corruption. This study aims to critically examine Islamic criminal law as a normative alternative framework for combating corruption, premised on the holistic character of fiqh jināyah in addressing both moral and structural dimensions of crime. Employing a qualitative method with a normative juridical approach, this research utilises statute and conceptual analyses based on secondary data derived from legislation, Islamic legal sources, and criminal law literature. The findings indicate that positive law has not comprehensively addressed corruption, thereby affirming the relevance of Islamic criminal law, which conceptualises corruption as jarīmah fasād grounded in Qur’anic principles and legal maxims, offering a stronger foundation for deterrence, justice, and social accountability.